Ethno Medicinal Knowledge and Practices in Gandhamardan Hills: An In-Depth Survey - Bal Nigamanand; Das Arun Kumar (International Journal of Ayurveda and Pharma Research, 2024)
This document lists twenty plant species that have historically been utilized to treat a variety of illnesses and health problems by the most well-known ethnic tribe in the Gandhamardan hill region. Firsthand information gathered from key tribal communities in the Gandhamardan hill region of the Balangir districts of Odisha through a number of surveys and field trips. A result of the ethno-medical study is presented, including local names, botanical names, families, locations of collecting, and methods of administration. The article highlighted the distinctive variety of plants found in this hill range and the actions necessary to protect the endangered species.